SKRINING PERKEMBANGAN ANAK USIA 4 – 6 TAHUN - Fredericksen Victoranto Amseke; Richard S. Tolang (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2025)
Child development is a process of change in a child towards the stage of maturity or maturity of physical and psychological functions that occurs within a certain period of time. Based on research at the Dahlia Christian Kindergarten, there are 3 out of 10 children who are still unable to retell the video they have watched, walking on tiptoe with both hands on their hips 3 meters away, catching and throwing a small ball 5 meters away. At the Dahlia Christian Kindergarten, there has never been an early growth and development detection test. The purpose of this writing is to determine the development of children aged 4-6 years at the Dahlia Christian Kindergarten in 2023. This research design uses descriptive quantitative methods. The research sample was children aged 4-6 years at the Dahlia Christian Kindergarten. This research was conducted at the Dahlia Christian Kindergarten using the Pre-Developmental Screening Questionnaire (KPSP). The results of the research found that the development category was appropriate as much as (70%), the development category was doubtful as much as (50%). The deviation development category is (30%). Nearly half of respondents were in the developmentally appropriate category. Advice for mothers and fathers is to always be more active in providing stimulation to children through gross motor skills and language so that children's development can take place more optimally.